Ponthieva hermiliae, a new species of orchidaceae in the cordillera yanachaga (Oxapampa, Pasco, Peru) - Valenzuela Gamarra, Luis (Lankesteriana: International Journal on Orchidology, 2013)
A new species of Ponthieva was found in the mountains of Yanachaga Chemillén, on a pre-montane forest at 1400 m in the central jungle of Peru. It is similar to P. pilosissima, but can be distinguished by the presence of a callus on the lip and by the color of the petals, which are boldly veined in P. pilosissima and inconspicuously striped in P. hermiliae.